Unleashing the potential of agricultural extension workers in Luwu Regency, Indonesia: an analysis of the role of personal factors, motivation, and competence in enhancing performance - Hasmita Hasmita; M Zainal; Ade Irma Surani Haliq (Universitas Lancang Kuning, 2023)
As agricultural development agents, agricultural extension workers play an essential role in empowering farmers. Improving the quality of extension workers is necessary to ensure that their performance is beneficial, especially for assisted farmers. This study aimed to analyze the influence of personal factors, motivation, and competence on the performance of agricultural extension workers in the Luwu Regency. The research employed quantitative methods with a survey approach. The study was conducted in six districts of Luwu Regency, including Belopa, Suli, Bajo, Kamanre, West Bajo, and Latimojong, from October to November 2022. A census technique was used to sample all populations, resulting in a sample of 53 agricultural extension workers. Data collection was carried out through questionnaires containing questions about research changes. The results revealed that agricultural extension workers in Luwu Regency were generally young and possessed high competence, which was dominated by the motivation for the need for power. The motivational factor of extension workers in Luwu Regency was a dominant aspect that significantly influenced the performance of extension workers. Meanwhile, the competence factor of agricultural extension workers, reflected by intellectual and social competence, had a real effect on the performance of extension workers, especially in evaluating agricultural extension.